Da’i Credibility in The Post-Truth Era: A Study of Da’i in Surabaya - Maulidatus Syahrotin Naqqiyah; Ali Nurdin (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2019)
The development of media technology and the level of one's ability to use social media to be one of the triggers for the birth of the post-truth era, an era in which too much truth will become a lie. Da'wah in the post-truth era requires the credibility of a competent preacher to bring people back so that they are not lulled by the flow of technological development. This study aims to describe the methods of da’i (Islamic preachers) in building and increasing their credibility in the post-truth era in Surabaya. The study conducted by  descriptive-qualitative and the data collection techniques used interview and observation. Data were analyzed by the perspective of the source credibility theory. The results of study describe that building and increasing its credibility, a da’i uses several methods applied in preaching in the post-truth era by including his scientific ‘sanad’ clearly, using the main literature as reference material such as classic books that are synergized with contemporary literature (internet), having written works that have been published, and sorting diction messages in accordance with mad’u or the communicant situation.   Perkembangan teknologi media dan tingkat kemampuan seseorang dalam menggunakan media sosial menjadi salah satu pemicu lahirnya era post-truth, yaitu era di mana sebuah kebenaran yang terlampau berlebihan akan menjadi sebuah kebohongan. Dakwah di era post-truth  memerlukan kredibilitas seorang da’i yang kompeten untuk membawa kembali masyarakat agar tidak terlena oleh arus perkembangan teknologi. Penelitian ini bertujuan untuk mendeskripsikan cara da’i dalam membangun dan meningkatkan kredibilitasnya di era post-truth di Surabaya. Penelitian dilakukan dengan jenis deskriptif-kualitatif dan teknik pengumpulan data dengan wawancara dan pengamatan. Data dianalisis dengan perspektif teori kredibilitas sumber. Hasil penelitian mendeskripsikan bahwa dalam membangun dan meningkatkan kredibilitasnya, seorang da’i menggunakan beberapa cara yang diterapkan dalam berdakwah di era post-truth yaitu dengan menyertakan sanad keilmuan yang dimilikinya dengan jelas, menggunakan literatur utama sebagai referensi materi, seperti kitab-kitab klasik yang disinergikan dengan literatur kekinian (internet), memiliki hasil karya tulis yang telah dipublikasikan, dan pemilihan diksi pesan yang sesuai dengan keadaan mad’unya.